Utopian Method: Reimagining Age Expectations and Intergenerational Relationships Through Reader Responses to Tove Jansson’s The Summer Book (1972) - French, Jade Elizabeth; Lovatt, Melanie; Wright, Valerie (Age, Culture, Humanities: An Interdisciplinary Journal, 2024)
We analyze reader responses to Tove Jansson’s The Summer Book to suggest the novel offers a platform from which to imagine new, often utopian, thresholds of aging and intergenerational relationships. We suggest the way literature encourages utopian thinking is two-fold, allowing readers to reflect on the current state of the world around them and encouraging them to reimagine new possibilities. The aim of the reading groups was to use the novel to reflect on current age norms – socially, culturally, and politically – and reimagine new social futures relating to intergenerational relationships. In this paper, we discuss the findings from using The Summer Book as a platform to discuss attitudes to aging, time, intergenerational relationships, and age expectations. Participants opened up a number of avenues to reimagine age expectations, categories, and relationships, whilst also relating the fiction to their own experiences, which then often translated into discussions of how age-based stereotypes and intergenerational relationships need to be radically rethought. There were three main themes that we identified from these discussions: 1) countering age-expectations on the intergenerational island, 2) creating counter-narratives through the character of the Grandmother, 3) using the novel’s relational behaviors and practices to imagine better futures for intergenerational relationships.